Specialized iron production in Roman times – metallographic examination of forging pre-product bars - Szilvia Gyöngyösi; Zsuzsanna Bánóczy; Géza Szabó (UISPP Journal)
In Roman times, according to sources, mining and metallurgy were organized and managed centrally. The area of Pannonia was supplied with iron ore from the Majdan Mountains from the early Iron Age onward, which was then largely processed according to needs by local blacksmiths. Particularly interesting questions are raised by the square column bars found at several sites in Southern Transdanubia. Similar finds were found in 1880 near Hrvatska Dubica in Croatia. Aleksandar Durman hypothesized Syrian influences in the production of iron bars, defined as Roman and about 20 cm long, forged to a weight of 11–15 libra, or 3.6–4.91 kg, based on finds found in the vicinity of the aforementioned site. In Pannonia, square column-shaped iron bars are known near the Danube (Intercisa – Dunaújváros) and the Kapos Valley (Dombóvár, Regöly), but they are heavier than the finds from Croatia, weighing 5.4–10 kg. Iron metallurgy is highly technology- and raw material-dependent, and is traditional in every detail, even from compulsion to ensure quality. Therefore, metallographic examinations play a particularly important role in research. A recent analysis of Pannonian square-bar bars shows that several pieces of bloom were forged during their production. Their microstructure is heterogeneous, typically ferrite-perlitic in which ferrite is found with Widmanstätten morphology. All indications are that the raw material blocks provided a standard good quality raw material for the production of different tools, weapons, etc.